O Racismo Institucional Contra os Negros na Polícia Militar - Arandas, Wagner Solano de (2010)
The present work aims firstly to pursue an interpretative analysis about instances of racism inflicted upon blacks by the Military Police. Although, there was an almost complete lack of data concerning the theme proposed here, a new strategy was developed to try and explain why these instances of racial discrimination were never reported and why data was neither collected by the Police and the Justice department nor included in arresting reports. Secondly, it reexamines the role of the Military Police in order to free it from outdated practices and to transform it into an institution that defends citizenship according to the Illuminist principles of human rights, without giving way to overtly ideological utopias. The need to recognize racism as a social issue goes far beyond the role of the Police. Nonetheless, an Institution that represents a Democratic State and its rights should not use such practices.